Xylo-oligosaccharides, fermentable sugars, and bioenergy production from sugarcane straw using steam explosion pretreatment at pilot-scale - Brenelli, Lívia B.; Bhatia, Rakesh; Djajadi, Demi T.; Thygesen, Lisbeth G.; Rabelo, Sarita C. [UNESP]; Leak, David J.; Franco, Telma T.; Gallagher, Joe A. (Elsevier, 2022)
This study investigated the production of xylo-oligosaccharides (XOS) from sugarcane straw (SCS) using steam explosion (SE) pretreatment at pilot-scale, as well as co-production of fermentable sugars and lignin-rich residues for bioethanol and bioenergy, respectively. SE conditions 200 °C; 15 bar; 10 min led to 1) soluble XOS yields of up to 35 % (w/w) of initial xylan with ∼50 % of the recovered XOS corresponding to xylobiose and xylotriose, considered the most valuable sugars for prebiotic applications; 2) fermentable glucose yields from the enzymatic hydrolysis of SE-pretreated SCS of up to ∼78 %; 3) increase in the energy content of saccharified SCS residues (16 %) compared to the untreated material. From an integrated biorefinery perspective, it demonstrated the potential use of SCS for the production of value-added XOS ingredients as well as liquid and solid biofuel products.
Keywords: Biofuels; Biorefining; Steam explosion; Sugarcane straw; Xylo-oligosaccharides